Por onde estamos caminhando no cuidado em terapia ocupacional em telessaúde? Um estudo qualitativo com terapeutas ocupacionais do Método Terapia Ocupacional Dinâmica - Lopes, Kezia (2024)
Telehealth was been promoted as a form of occupational therapy care in the context of the COVID-19 pandemic. Given this new scenario, it would be interesting to understand how these services are being conducted and how theoretical-methodological frameworks are being employed. The Dynamic Occupational Therapy Method (MTOD) is a theoretical-methodological framework that has been developed in Brazil since the 1970s and is aimed at clinical practice. Objective: To understand how the Dynamic Occupational Therapy Method is being used in the telehealth modality. Methodology: Qualitative exploratory research. The participants consisted of 13 occupational therapists trained in the MTOD methodology who provide services via telehealth. Data were collected through participant characterization forms and semi-structured individual interviews. Data analysis was conducted using the thematic analysis method. Results: Telehealth expanded the reach and possibility of a new modality, facilitating access to occupational therapy services. The MTOD provided theoretical-methodological support for the occupational therapists. The difficulty regarding the virtual skills of the occupational therapist impacted the activities. Discussion: There is a need to expand our knowledge of technologies, identify the target subjects to be served, and determine which regulations to follow. Final Considerations: The MTOD has proven to be a theoretical-methodological framework for occupational therapy that can be used in the telehealth modality due to its dynamic and flexible nature, favoring access to target subjects from various locations and expanding the possibilities of activities with technological resources.